FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN STUNTING PADA BALITA DI WILAYAH KERJA PUSKESMAS TANJUNG TIRAM KECAMATAN TANJUNG TIRAM KABUPATEN BATU BARA TAHUN 2013 - novita siahaan; Zulhaida Lubis; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
Stunting is a public health problem because associated with an increased risk of morbidity,mortality, and impaired motoric and mental development. Stunting is a condition of the body isshort and very short (-2 SD below the median length or height of body). Purpose of this study is toknow the factors releated with stunting among under five children at Tanjung Tiram in 2013.This study is survey with cross-sectional design in 3 selected villages in the district TanjungTiram. The determination of sample is done in allocation proportion and selected by systematicrandom sampling with 93 under five children samples. Variabel of house hold members, educationof parent, birth weight, economic status, breast feeding practice and employment of parent weremeasured using questionaires and height of body were measured by microtoise, then dataanalyzed using by Chi- Square test at =0,05.The result of the research showed that based on index TB/U stunting among under fivechildren 59,14%. The result of Chi-Square test showed significant relationship between stuntingwith education of parent, economic status, and employment of parent. Meanwhile number ofhousehold and birth weight did not show significant relationship of stunting in under five children.It is recommended to local government in order to improve education of parents with KejarPacket C and revitalize the fishing’s coperation to enhance the economic status.Key word : Stunting, Economic Status, Under Five Children.